Effects Induced by a Weak Static Magnetic Field of Different Intensities on HT‐1080 Fibrosarcoma Cells - Gurhan, Hakki; Bruzon, Rodolfo; Kandala, Sahithi; Greenebaum, Ben; Barnes, Frank (Bioelectromagnetics, 2021)
In this study, we investigated the effects of weak static magnetic fields (SMFs) on HT‐1080 human fibrosarcoma cells. Exposures to SMFs for four consecutive days were varied from 0.5 to 600 µT for treated units, while exposures to control units were held at 45 µT. Growth rates were measured by comparing cell counts, whereas membrane potentials, mitochondrial calcium, mitochondrial superoxide (O2−), nitric oxide (NO), hydrogen peroxide (H2O2), intercellular pH, and oxidative stress were measured by using fluorescent dyes. The relative cell growth rates vary with the angle of the SMFs. Increases in the magnitude of the SMFs increased concentrations of mitochondrial calcium and membrane potential and decreased intracellular pH. H2O2, an important reactive oxygen species (ROS), increases at 100 and 200 µT, decreases at 300 and 400 µT and increases again at 500 and 600 µT. Overall, oxidative stress increases slightly with increasing SMFs, while superoxide and NO concentrations decrease. These results indicate that weak SMFs can accelerate and inhibit cell growth rates and induce alterations in ROS. Changes in ROS and oxidative stress are important for various cell functions. Calcium influx into mitochondria was one of the initial steps into the corresponding changes. Bioelectromagnetics. 2021. © 2021 Bioelectromagnetics Society